2011
DOI: 10.1016/j.acap.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Medical Records (EMRs), Epidemiology, and Epistemology: Reflections on EMRs and Future Pediatric Clinical Research

Abstract: Electronic medical records (EMRs) are increasingly common in pediatric patient care. EMR data represent a relatively novel and rich resource for clinical research. The fact, however, that pediatric EMR data are collected for the purposes of clinical documentation and billing rather than research creates obstacles to their use in scientific investigation. Particular issues include accuracy, completeness, comparability between settings, ease of extraction, and context of recording. Although these problems can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 36 publications
0
71
0
Order By: Relevance
“…1 The expansive range of information and the sheer volume permitting the identification and evaluation of outcomes gathered is appealing for application in a research environment. 2, 3 Combining data from diverse clinical setting also strengthens the generalisability of findings.…”
Section: Introduction and Objectivementioning
confidence: 99%
“…1 The expansive range of information and the sheer volume permitting the identification and evaluation of outcomes gathered is appealing for application in a research environment. 2, 3 Combining data from diverse clinical setting also strengthens the generalisability of findings.…”
Section: Introduction and Objectivementioning
confidence: 99%
“…11,12 Data collected during routine clinical care can be extracted and reused to support patient-centered and population-based clinical care management, quality reporting, and clinical research. 6,13,14 The concept of "enter once, use many times" has enormous appeal and potential, especially given the high cost of dedicated single-purpose data collection or chart abstraction. 15,16 A clinical research project that develops its own data definitions, data collection forms, and protocols specific to the unique population, interventions, and outcomes has effectively developed its own independent "language" to convey the meaning of concepts being studied.…”
mentioning
confidence: 99%
“…As resources for largescale, long-term sustainable child health research become more limited, efforts that can leverage previous investments are both timely and necessary. 13,14 Study-specific terminology may reflect evolving understanding of conditions being studied. But these one-off terminologies also arise in significant part from the limited adoption of standardized controlled terminologies in pediatric research, a technology that can reduce or eliminate data silos and enhance data reuse and integration.…”
mentioning
confidence: 99%
“…An ongoing technical support and renovation of the hardware must be provided in order to overcome these issues and facilitated the transition and adoption process of an EHR system and help the physicians to effectively utilize it. Similar studies have identified other benefits of using the EHRs for pediatricians, including the impact on pediatric clinical research and pediatric quality improvement projects [21].…”
Section: Opinions Of Pediatriciansmentioning
confidence: 99%